2017
DOI: 10.4168/aair.2017.9.4.368
|View full text |Cite
|
Sign up to set email alerts
|

Real-life Efficacy of Omalizumab After 9 Years of Follow-up

Abstract: Omalizumab is frequently used as add-on treatment to inhaled corticosteroids (ICS) and long-acting β2-agonists in patients with suboptimal control of severe asthma. Patients with severe asthma will typically require chronic treatment, although due to the limited amount of data available there are still some concerns about the safety and efficacy of long-term therapy with omalizumab. Herein, in an extension of a previous 4-year study, we report disease-related outcomes of 8 patients with severe persistent aller… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
55
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(68 citation statements)
references
References 16 publications
6
55
0
2
Order By: Relevance
“…Omalizumab add-on treatment in the Czech Republic sub-population resulted in considerable reductions in the daytime and nocturnal symptoms, limitations of activities, and rescue medication use, which was comparable with results seen in the overall population of the eXpeRience registry and other real-life studies [10,11,13,[25][26][27][28][29]. There was also a considerable reduction from baseline in the number of patients on OCS maintenance therapy (n = 38) to 24 months after the treatment (n = 18) along with a 44.8% reduction in the total daily dose from 11.6 mg at baseline (prednisolone equivalent) to 6.4 mg at month 24.…”
Section: Discussionsupporting
confidence: 67%
“…Omalizumab add-on treatment in the Czech Republic sub-population resulted in considerable reductions in the daytime and nocturnal symptoms, limitations of activities, and rescue medication use, which was comparable with results seen in the overall population of the eXpeRience registry and other real-life studies [10,11,13,[25][26][27][28][29]. There was also a considerable reduction from baseline in the number of patients on OCS maintenance therapy (n = 38) to 24 months after the treatment (n = 18) along with a 44.8% reduction in the total daily dose from 11.6 mg at baseline (prednisolone equivalent) to 6.4 mg at month 24.…”
Section: Discussionsupporting
confidence: 67%
“…However, in a recently published study the additional improvement of the asthma after longer omalizumab treatment, that is, more than 16 weeks, showed that although the majority of patients responded already at 16 weeks (defined as ''fast responders'') some patients did require longer treatment that is, 24 weeks (defined as ''slow responders'') for more successful outcome [22]. Another study of omalizumab treatment efficacy on quality of life and FEV1% found that the efficacy gradually increased from baseline to 32 weeks and 4 and 9 years [23].…”
Section: Discussionmentioning
confidence: 99%
“…Длительное непрерывное лечение омализумабом улучшает контроль над болезнью, переносимость физи-ческой нагрузки, сокращает потребность в КДБА и слу-чаи тяжелых обострений, имеет высокий профиль безо-пасности [29].…”
unclassified